1990
DOI: 10.1007/bf00400209
|View full text |Cite
|
Sign up to set email alerts
|

The first phase insulin response to intravenous glucose is highly reproducible

Abstract: To determine the reproducibility of the first phase insulin response to intravenous glucose, ten normal subjects underwent two intravenous glucose tolerance tests separated by at least two weeks. Intravenous dextrose (0.3 g/kg) was administered over 2 min by continuous infusion and arterialised-venous samples were taken from a retrogradely cannulated hand vein in the opposite arm. Within subjects, median coefficient of variation for the 3 min insulin was 4.0% (range 1.2-24.3%) and median coefficient of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 8 publications
0
17
1
Order By: Relevance
“…We have shown that this measurement of first phase insulin release is highly reproducible [11]. In addition the first phase insulin response has been shown to correlate with both the pancreatic insulin content and beta-cell mass [14].…”
Section: Discussionmentioning
confidence: 79%
“…We have shown that this measurement of first phase insulin release is highly reproducible [11]. In addition the first phase insulin response has been shown to correlate with both the pancreatic insulin content and beta-cell mass [14].…”
Section: Discussionmentioning
confidence: 79%
“…3 additionally shows results of an oGTT of son I using a 100-g glucose load, demonstrating an impaired response to this challenge. ivGTTs have been established to provide a sensitive index of ␤ cell function, particularly with regard to the rapid first-phase insulin response (28). Therefore, results of ivGTTs were evaluated for insulin secretion, especially the first-phase peak, and glucose elimination.…”
Section: Resultsmentioning
confidence: 99%
“…For ivGTTs, 0.33 g glucose/kg body wt was injected intravenously as a 40% solution into the right antecubital vein within 2 min. Blood for insulin and C-peptide was drawn from a permanent cannula placed into the left radial vein while keeping the hand in a water bath at 44 Њ C, to obtain arterialized blood as suggested elsewhere (28). Samples were drawn at 0, 1, 2, 3, 4, 5, 6, 8, 10, 20, 40, and 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…Insulin sensitivity (Si) has been found to be closely correlated to the glucose disposal rate measured by the euglycemic hyperinsulinemic clamp (40)(41)(42). Furthermore, the reproducibility of Si and the acute insulin response to glucose has been found to be sufficient (43,44). One further advantage of the FSIGT is the simultaneous estimation of insulin secretion, insulin sensitivity, and glucose-mediated glucose disposal.…”
Section: Discussionmentioning
confidence: 99%